Aspergillus fumigatus spondylitis in an immunocompetent patient with annular high signal around the intervertebral disks: a case report and literature review - Xu, Zhihao; Zhu, Weijian; Zhou, Sirui; Zhao, Yuting; Xiang, Qi; Zhang, Yi (Frontiers in Medicine, 2025)
Aspergillus fumigatus spondylitis is a rare fungal infection, primarily occurring in immunocompromised patients, although cases in immunocompetent individuals have also been reported. While Aspergillus fumigatus is commonly associated with pulmonary infections, it can also cause spondylitis. Patients typically present with back pain, limb numbness, and neurological compression symptoms. Imaging findings often show vertebral destruction, reduced disk height, and paraspinal abscesses, potentially accompanied by characteristic ring-enhancing lesions. MRI findings can help distinguish Aspergillus fumigatus spondylitis from other conditions such as tuberculous spondylitis. This case involves an immunocompetent patient with Aspergillus fumigatus spondylitis, whose non-specific clinical manifestations can easily be confused with other types of spinal infections, leading to a potential misdiagnosis. Diagnosis requires tissue biopsy and microbiological culture. Voriconazole is the first-line antifungal agent, and studies have shown that it improves patient response and survival rates. For patients with significant spinal compression or neurological symptoms, surgical intervention combined with antifungal treatment should be considered if antifungal therapy alone is ineffective. Although Aspergillus fumigatus spondylitis is rare, it can occur in immunocompetent individuals. Early diagnosis through imaging and biopsy is crucial, and a combination of surgery and antifungal therapy can help improve prognosis.